Modifiable Risk Factors of Non-Syndromic Orofacial Clefts: A Systematic Review - Angelo Michele Inchingolo; Maria Celeste Fatone; Giuseppina Malcangi; Pasquale Avantario; Fabio Piras; Assunta Patano; Chiara Di Pede; Anna Netti; Anna Maria Ciocia; Elisabetta De Ruvo; Fabio Viapiano; Giulia Palmieri; et al. (MDPI AG, 2022)
OFCs (orofacial clefts) are among the most frequent congenital defects, but their etiology has yet to be clarified. OFCs affect different structures and functions with social, psychological and economic implications in children and their families. Identifying modifiable risk factors is mandatory to prevent the occurrence of non-syndromic OFCs (NSOFCs). PubMed, Cochrane Library, Scopus and Web of Science were searched from 1 January 2012 to 25 May 2022 and a total of 7668 publications were identified. Studies focusing on the risk factors of NSOFCs were selected, leading to 62 case-control and randomized clinical trials. Risk factors were categorized into non-modifiable and modifiable. The first group includes genetic polymorphisms, gender of the newborn, ethnicity, and familiarity. Within the second group, risk factors that can only be modified before conception (consanguinity, parental age at conception, socio-economical and educational level, area of residency and climate), and risk factors modifiable before and after conception (weight, nutritional state, acute and chronic diseases, psychophysical stress, licit and illicit drugs, alcohol, smoke, pollutants and contaminants) have been distinguished. This study provides a wide overview of the risk factors of NSOFCs, focusing on modifiable ones, to suggest new perspectives in education, prevention, medical interventions and clinical research.